2000
DOI: 10.1007/s002640000127
|View full text |Cite
|
Sign up to set email alerts
|

The value of a new method for assessing the separate functions of the long tracts and involved segments in patients with cervical myelopathy

Abstract: In order to assess accurately lesions of the spinal cord in patients with cervical myelopathy we have developed a new method of examination, which is based on the Japanese Orthopaedic Association (JOA) scoring system. The method attempts to assess separately the functions of the long tract and any involved cord segments in respect to the period after treatment. It was used in 117 consecutive patients who were divided into 2 groups based on whether or not there was a T2-highintensity lesion within the spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Our results indicate that it is critical to consider quantitative sensory impairment in addition to measuring strength and dexterity in the neurological assessments of mild DCM patients, as loss of sensation is the primary complaint among these patients [20] and early in the disease progression reduced sensation is the main factor contributing to UL disability. A similar set of relationships is seen when the group is stratified by UL mJOA, however, sensation plays a significant role in both mild and moderate severity with this classification of the mJOA [16]. All three components of impairment remained significant through the mild and moderate ranges of severity, again leaving strength as the single significant factor at the severe stage.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our results indicate that it is critical to consider quantitative sensory impairment in addition to measuring strength and dexterity in the neurological assessments of mild DCM patients, as loss of sensation is the primary complaint among these patients [20] and early in the disease progression reduced sensation is the main factor contributing to UL disability. A similar set of relationships is seen when the group is stratified by UL mJOA, however, sensation plays a significant role in both mild and moderate severity with this classification of the mJOA [16]. All three components of impairment remained significant through the mild and moderate ranges of severity, again leaving strength as the single significant factor at the severe stage.…”
Section: Discussionmentioning
confidence: 56%
“…The mJOA stratification followed previously defined cut points of the DCM population (5). A second stratification was performed to be more specific in relation to the UL (mJOA UL), as previously characterized [16]. The UL sensation and UL motor subscores of the mJOA were summed and used to stratify the sample for the analysis of duration of symptoms to ensure the deficit was specific to the upper limb.…”
Section: Methodsmentioning
confidence: 99%
“…Hirabayashi et al assumed that the degree of function of the upper limbs in patients with T2-high intensity lesion revealed more about a segment than about the long tract [18].…”
Section: Discussionmentioning
confidence: 99%
“…30 All our patients were followed up postoperatively at 2 time points (6 and 12 mo), considered to be the optimal points in recovery after decompressive surgery. Our study found that both STS and LTS functions are affected equally (with similar correlation coeffi cients, both being statistically signifi cant) when the spinal cord is compressed.…”
Section: The Separate Functions Of the Long Tracts And Involved Segmentsmentioning
confidence: 99%